Interacting Among Us : Promoting English Oral Interaction Through the Use of a Video Game in an Online Class (2021)
ABSTRACT:This action research project was developed during the transition between online and face-to- face classes in a public school in Medellín. Due to the health situation and the restrictions established by the Colombian government, during most of the current year online classes were given in the public institution INEM José Félix de Restrepo, where this study was conducted. Its main objective was to use video games to improve online interaction among students during class time, using a Game-based teaching approach. The methods to gather data include a survey, online class recordings and interviews for a subsequent analysis. The results show how with the video game students had more opportunities to interact in a comfortable environment during online classes.